Vitamin C in the Diet of Inuit Hunters From Holman, N.W.T. - Geraci, Joseph R.; Smith, Thomas G. (ARCTIC, 1979)
During the spring and summer months the diet of three Inuit families living in a seal hunting camp south of Holman, N.W.T., was studied. A total of 13 food items including the most commonly eaten mammal, bird and plant species were analysed for Vitamin C in both the raw and cooked state. We document a daily intake of ascorbic acid of between 11 and 118 mg and estimate a mean dose of at least 30 mg. This is well above the levels documented in larger transitional culture villages by a recent Nutrition Canada report.